THE ISSUES OF ENSURING SECURITY OF THE STATE BORDER THROUGH SUBSURFACE BORDER PROTECTION - Erdenetsogt Gochoosuren; Ganbileg Alagdaa (International Journal of Innovative Technologies in Social Science, 2025)
This article highlights the significance of subsurface border protection for national security, including border security. The study points out that enhancing the legal framework for subsurface border protection and establishing a security system can effectively implement an integrated border protection system. Mongolia’s border security comprises three main components: surface, air, and underground borders. However, the absence of subsurface border protection has been shown to adversely affect national security. Subsurface border protection refers to the security measures and operations that safeguard areas beneath the surface, such as underground tunnels or voids that could be used for smuggling or illegal crossings. It is part of a larger operational system that includes the protection of surface and air borders through coordinated efforts in various domains such as political, legal, and intelligence activities. The threat of subsurface breaches is an important aspect of overall border security. Therefore, enhancing subsurface border protection is crucial for ensuring national security, and an integrated solution involving technological solutions, legal regulations, and international cooperation is necessary.